2013
DOI: 10.1155/2013/817674
|View full text |Cite
|
Sign up to set email alerts
|

Subtoxic Levels of Apigenin Inhibit Expression and Secretion of VEGF by Uveal Melanoma Cells via Suppression of ERK1/2 and PI3K/Akt Pathways

Abstract: The effects of apigenin on the expression of VEGF in uveal melanoma cells have not been reported. We studied this effect and relevant signaling pathways in two human uveal melanoma cell lines (SP6.5 and C918). ELISA assay revealed that the constitutive secretion of VEGF by uveal melanoma cells was 21-fold higher than that in normal uveal melanocytes. Apigenin at subtoxic levels (1–5 μM) significantly suppressed the secretion of VEGF in a dose- and time-dependent manner in melanoma cells. VEGF levels in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…For the pathogenesis, on-cogenes such as K-ras and c-erbB2 (both act as important roles in the MAPK signal pathway) may mutate in gastric cancer (Nagini, 2012), causing abnormal growth cycle in gastric cells, and at the same time, vascular endothelial growth factor (VEGF), related to invasion and angiogenesis by reducing cellcell adhesion is found over-expressed in the cancer cells (Nagini, 2012;Chao et al, 2013). Experiments showed that once the P38MAPK was inhibited.…”
Section: Mapk and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…For the pathogenesis, on-cogenes such as K-ras and c-erbB2 (both act as important roles in the MAPK signal pathway) may mutate in gastric cancer (Nagini, 2012), causing abnormal growth cycle in gastric cells, and at the same time, vascular endothelial growth factor (VEGF), related to invasion and angiogenesis by reducing cellcell adhesion is found over-expressed in the cancer cells (Nagini, 2012;Chao et al, 2013). Experiments showed that once the P38MAPK was inhibited.…”
Section: Mapk and Gastric Cancermentioning
confidence: 99%
“…And phosphorylation of the JNK may also be positively relative to cell proliferation and the VEGF expression. But activation of the ERK1/2 and PI3K/ Aktpathways were thought to be the vital one in tumor progression (Chao et al, 2013). In some case, VEGFdependent tumor angiogenesis is resulted by interaction of VEGFR1 and VEGFR2 (Zhang et al, 2010), while it is also believed that VEGFR1 signaling is responsible for endothelial cell survival, but VEGFR2 regulates capillary tuber formation (Zhang et al, 2010).…”
Section: Mapk and Gastric Cancermentioning
confidence: 99%
“…In addition, preparations from chamomile have been historically used to treat cutaneous inflammation and other dermatological diseases [251]. Apigenin has been identified as a cancer chemopreventive agent owing to its potent antioxidant, anti-melanoma and anti-inflammatory activities with low toxicities [252, 253]. In two separate studies, Caltagirone et al [154] and Piantelli et al [254] found that apigenin inhibited melanoma tumor growth (B16-BL6 melanoma cells) in vivo and inhibited VEGF secretion by downregulating ERK1/2 and PI3K/AKT signaling in vitro [252].…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…Apigenin has been identified as a cancer chemopreventive agent owing to its potent antioxidant, anti-melanoma and anti-inflammatory activities with low toxicities [252, 253]. In two separate studies, Caltagirone et al [154] and Piantelli et al [254] found that apigenin inhibited melanoma tumor growth (B16-BL6 melanoma cells) in vivo and inhibited VEGF secretion by downregulating ERK1/2 and PI3K/AKT signaling in vitro [252]. Moreover, apigenin significantly decreased the invasion of melanoma cells in vitro and inhibited lung metastasis in vivo by reducing lung colonization of B16-BL6 cells in mice [154, 254].…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
“…These cells can be found in skin, but also in other parts of the body, including the bowel and the eye. Uveal melanoma is also an entity that has been reported 2,3. Melanoma can originate in any part of the body that contains melanocytes.…”
Section: Introductionmentioning
confidence: 99%